Spontaneous Expulsion of Intramural Fibroid Six Weeks after Emergency Caesarean Section - Balvinder Sagoo; Ka Ying Bonnie Ng; G. Ghaleb; Heather Brown (Case Reports in Obstetrics and Gynecology)
We present a thirty-six-year-old woman with a high risk pregnancy, complicated by multiple congenital anomalies, severe hyperemesis, a pulmonary embolus, and a large intramural fibroid. This fibroid grew in size during the pregnancy. At 34 + 5 weeks, there were reduced fetal movements and a pathological CTG. A live infant was delivered by an emergency cesarean section. Five weeks postpartum, she presented with abdominal pain, offensive vaginal discharge, and fevers. She was given antibiotics and ferrous sulphate. An abdominal ultrasound showed an 11 × 12 × 9 cm fibroid with a coarse degenerative appearance. Clinically, she showed signs of sepsis; a CT scan and laparotomy performed under general anesthetic did not find any collections as a source of sepsis. When stable, she was discharged. She re-presented two days later with a large mass (necrotic fibroid) in her vagina. This is the first case of spontaneous expulsion of fibroid six weeks after caesarean section. Presentation of pain and fever after the delivery may be due to red degeneration of the fibroid, caused by diminished blood supply, ischaemia, and necrosis. This case highlights the importance of considering fibroids as a cause for abdominal pain during and after pregnancy, even up to 6 weeks after delivery.